Forest management in Central Africa: where are we? - Nasi, Robert; Cassagne, B.; Billand, A. (2006)
Today in the Central Africa region, production forests under management cover an area similar to that of protected forests. This is the result of a complex process initiated about 10 years ago, after a long gestation history and a sudden increase in speed in the mid 90s. Managed forests should be considered as an essential complement to the fundamental role of protected areas in their efforts to conserve the rich biodiversity of the region, as well as a significant contributor to economic development. In this paper the authors present new and updated figures about forest management in Central Africa as well as critical points to be addressed if we want to see progress towards better management and conservation.